A compact nonlinear dynamic analysis technique for transmission line cascades. (1st March 2018) - Alminhana, Fábio; Mason, Matthew; Albermani, Faris
Highlights: A compact dynamic analysis technique to model transmission lines sections is proposed. The technique incorporates geometric and material nonlinearities of lattice towers. The method was validated with results of full-scale tests. Abstract: Progressive failures, or cascades, have played a major role in numerous transmission system collapses around the globe during severe wind and ice storms. The failure of a line component overloads the system and initiates a failure sequence that can cause the collapse of many towers. This article describes the development of a special-purpose nonlinear dynamic analysis technique for the modelling of multi-span line sections under progressive failure scenarios. This method performs time-domain analysis based on a central finite difference scheme, adapted for a non-constant time increment. All the main line components are incorporated in the analysis. In particular, a special beam-column element is employed to describe geometric and material nonlinearities of angle members in steel lattice towers. The method is validated using full-scale test results for a single lattice tower and a line section containing seven towers.